Cutting Machine Manufacturing Design Process - Mikhael Sianipar, Binsar; Pradana, Sigit; Prayitno, Sugeng; Hadi Suryo, Taufik (Journal of Applied Science, Engineering, Technology, and Education, 2023)
On development, technology created For make it easy work man. In the process of making potato sticks , the cutting process is still done manually using simple cutting tools and human power. This counts less effective in terms of time, security, as well as capacity Which generated. Therefore it is necessary to make a potato stick cutting machine to help produce potatoes. So that this thesis takes the theme "Design Build a Potato Stick Cutting Machine ” which will focus on the process manufacture of the machine. Machine manufacturing process made based on terms of time, cost, and materials used. In the process of making this machine there is a number of component Which need made through process machining, welding, painting, as well as assembly. So that results end process manufacture obtained the value of time and cost of making a potato stick cutting machine and the capacity of tool the.